Improving Language Skills Through Arabic Strengthening Strategy/ ترقية المهارات اللغوية من خلال استراتيجية تقوية اللغة العربية - Bahruddin, Uril; Musthafa, Izzuddin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
One of the strategies that has succeeded in improving students' language skills, carried out by STIBA Ar-Rayah Sukabumi Indonesia, is the Arabic reinforcement program for new students who find it difficult to learn Arabic. This study aims to describe the strategy of the Arabic Reinforcement program and its impact on improving the language skills of new students who start learning Arabic. This study uses a qualitative approach with the type of case study research of the Arabic Reinforcement program strategy for new students of STIBA Ar-Raya. Data was collected through observations, interviews, document studies, and questionnaires distributed to students. Data is analyzed simultaneously, starting from data collection, condensation, presentation, and concluding. The results of this study are: (1) The Arabic Reinforcement strategy is a type of student activity that varies from repeating the material taught in class, providing language materials, and providing additional materials, all of which are adjusted to the needs of students. (2) The Arabic Reinforcement strategy shall be implemented outside of lecture hours, on effective days or weekends, in the afternoon or evening, under the supervision of the Head of the Language Preparation Department, for fifty minutes after agreement with the student. (3) The Arabic Reinforcement strategy improves students' four language skills: listening, speaking, reading, and writing. The conclusion of this study shows that additional academic activities contribute to increasing students' confidence in the use of Arabic so that such programs can be implemented in other Arabic language teaching institutions.